Optimisation of perioperative investigations among elective orthopaedic patients in a Dublin-based teaching hospital. Issue 9 (September 2019) - O'Sullivan, Jane; Collins, Jack; Cooper, David; Magdalina, Ana; Meehan, Frances; Kumar, Lachmann; Quinlan, John; O'Connor, Donal; Fitzpatrick, Gerry
Background: The current National Institute for Health and Care Excellence guidelines, in accordance with the Association of Anaesthetists of Great Britain and Ireland guidelines, recommend the following haematological investigations for all patients undergoing major elective surgery: full blood count, renal profile and coagulation screen if clinically indicated. However, the guidelines fail to specify a time-interval for which normal blood results remain valid. Currently all patients in Ireland undergoing substantial elective surgery requiring general or regional anaesthetic have a preoperative assessment prior to the surgery. Patients have phlebotomy performed as part of this assessment. Patients admitted for elective surgery often have these bloods repeated on the morning of surgery. Objectives: To determine if blood investigations taken over a one-year period prior to surgery can be used as a baseline for clinically stable patients undergoing elective surgery. Study design and methods: All consecutive day of surgery admission patients >18 years of age undergoing elective orthopaedic surgery in Tallaght Hospital between 1 December 2014 and 1 December 2015 were identified using hospital records. Their blood results in the one-year period prior to surgery were compared to the blood results on the morning of surgery, using a McNemar's test. A further clinical analysis was performed. Results: There was no statistically significant change between blood results from three months prior to the surgery and the morning of surgery (P < 0.05). Furthermore, the blood results remained largely unchanged in the one year prior to surgery. No patient had the operation deferred due to aberrant blood results, following previously normal results prior to surgery. The potential cost-saving of omitting bloods is enormous. Conclusions: There appears to be neither a statistical nor clinical benefit to repeating blood tests on the morning of surgery, following normal bloods <3 months in a clinically stable individual.